Analysis of Understanding Concepts and Mastery of Basic Competence of Thermochemistry Materials Post Use of Chemlovers Media - Puji Ningrum; Ariyatun Ariyatun (Tadris Biologi Fakultas Ilmu Tarbiyah dan Keguruan IAIN SYEKH NURJATI CIREBON, 2022)
The purpose of this study is to learn more about the level of conceptual understanding and academic competition among students studying chemistry material in thermochemistry by utilizing Chemlovers as a media and student body. Penelitian is carried out using a combined method of sequential explanation and data collection in two phases, namely quantitative and qualitative phases. Approximately 144 students from kelas XI of the MIPA SMA Negeri 10 Semarang participated in the survey. Understanding of concepts and demonstration of competency with regard to thermochemistry material was conducted using a three-tier multiple-choice test. Students’ disagreement with the media's use of Chemlovers comes from their angry response. The study's findings indicate that the percentage of respondents who understood the concept well was very high, with a score of about 66,74% (top category), and a score of 7,45% (low category). The level of student mastery of thermochemistry material, 80.56% of students fulfilled the minimal completeness criteria, with the highest score of 92.50, the lowest at 58.67, and an average of 83.37. Based on the results of this study, it can be said that media like Chemlovers efficiently helps students comprehend ideas and hone analytical abilities linked to thermochemistry. Respondents' comments on the utility of this android-based media were generally favorable.